Verb Aspect in Masbateño Discourse - Wolfenden, Elmer (The Archive; Vol 4 (1984): Publication Four: Studies on Philippine Minor Languages, 2025)
When analyzing a discourse or text it has proven helpful to identify the various kinds of information found in order to distinguish the significant from the peripheral, supporting, information. [...] Now, Longacre (1981), following the same line of investigation, suggests that even the differences in verb inflections may be correlated with different types of information in a discourse. He proposes the setting up of a cline of verb relevance for narrative discourse. Most relevant, and therefore occurring highest on the cline, would be the verb forms used in backbone sentences. Other verb forms occurring in the various types of non-backbone sentences would be assigned succeedingly lower places on the cline as less relevant. Furthermore, he postulates that different discourse types will have different clines of verb dynamism, which in turn may provide diagnostic clues for distinguishing discourses. This paper reports on a study of verb usage in narrative, explanatory, and hortatory discourse investigating the feasibility of such verb clines for Masbateño.